Journal of Policy Science (2016)
Vol. 11, 2017Isu khuhus edisi kali ini berjudul Seeking to Exploit the Potential of the Notion of ‘a Societal Cycle from Energy to Welfare’ in the North East Asia Region (hal. 1). Artikel lain di antaranya: Current Trends in Russian Education (hal. 5); Energy Security as a Tool of Political Pressure in a Protracted Conflict: impact of ownership of energy resource on welfare of population in Modolva including transdniestria (hal. 13); Creation of a Circulatory Energy and Welfare Regional Network and Avoidance of Conflict: the case of Russia’s Sakhalin Oblast (hal. 23); Welfare System in Contemporary Russia and Its Implication for Sakhalin Region (hal. 37); Globalizing Welfare (hal. 47); Why Pro-democracy Movement Can’t Bring their Country to Democracy: relation between pro-democracy movement and public sphere (hal. 61); Natural Gas Trade between the Soviet Union and Western Countries (hal. 69).